Implementasi Manajemen Resiko Pasar Pada Baitul Mal Wat Tamwil Agawe Makmur Tulungagung - Sari, Lella Juniva (Musyarakah: Journal of Sharia Economic (MJSE), 2023)
This research aims to find out how to manage market risk at BMT Agawe Makmur. Currently, BMT has made progress, but still often faces problems such as lack of member participation, lack of capital, poor risk management, and lack of supervision. This problem is an identifiable risk, so you should carry out risk mitigation based on the problems above. One of the risks often faced by financial institutions is market risk. Market risk is the risk of loss from on and off-balance sheet positions arising from market price movements. In accordance with the research results, it was found that in the risk management carried out by BMT Agawe Makmur Tulungagung, BMT implemented a way to deal with market risk, namely in the form of not considering rising prices or rising other things such as rising and falling interest rates. This is based on BMT Agawe Makmur, a financial institution that has sharia principles. In accordance with the discussion regarding BMT Agawe Makmur regarding the risks it faces, it can be seen that BMT Agawe Makmur has taken steps to overcome risks.